Study In Silico Compounds In 96% Ethanol Extract of Chrysanthemum cinerariifolium (Trev.) Leaves Towards Alfa Estrogen Receptors - Roihatul Mutiah; Yen Yen Indrawijaya; Dwi Puspita (Indonesian Journal of Cancer Chemoprevention, 2020)
Chrysanthemum cinerariifolium (Trev.) is a plant that has potential as an anticancer. This study aimed to predict the inhibitor of estrogen alpha and toxicity of compounds in 96% ethanol extract of C. cinerariifolium leaves in silico. Prediction of the activity of metabolic profiling compounds produced by UPLC QToF MS/MS ethanol extract 96% of C. cinerariifolium leaves towards alpha estrogen receptors (ER-α) (5W9C) was carried out using Molegro Virtual Docker. The docking results showed that the compound (2-Methyl-1,4-piperazinediyl) bis-[(3,4,5-trimethoxyphenyl)-methanone and Azoxystrobin have good activity compared to Tamoxifen, because these compounds have a lower Rerank Score. The activity of the test compound is also shown by the bonding of active amino acids (Arg 394, Asp351, Glu 353, and Val 533). As for the toxicity class based on Globally Harmonized System (GHS) and Lethal Dose 50 (LD50) values, the ten docking compounds had a relatively low toxicity.Keywords: C. cinerariifolium, breast cancer, alpha estrogen, cytotoxic activity, toxicity